Why don't buyers like electronic reverse auctions? Some insights from a French study. (4th June 2012) - Peng, Lilan; Calvi, Richard
This article aims to illustrate the resistance to change from the buyers' side that is related to the application of electronic reverse auction (ERA) in organisations. Our article focuses on the relation between the tool and the buyers. ERA brings significant changes to the purchasing process. When the method is introduced to the field, the resistance to change occurs not only from the suppliers' side, but also from the buyers' side. It seems that many buyers do not like ERA, and most of them will not use ERA spontaneously. There is a reluctance to change from the buyer's side, both at the pilot phase and sporadic phase. From this exploratory research, we also identify six reasons for this reluctance. This conclusion is deduced from a qualitative survey carried out with ERA experts from top retailer groups (Auchan, Carrefour, Casino, Castorama) and two e–procurement consulting companies in France.